2013
DOI: 10.21608/aeji.2013.17313
|View full text |Cite
|
Sign up to set email alerts
|

How Morocco Succeeds in Eliminating Schistosomiasis

Abstract: Schistosomiasis is an endemic parasitic infection very linked to poverty. It is considered a world health problem since it infects people from 76 different countries especially tropical and subtropical regions. For many years, Morocco was endemic for shistosome infection. The unique form is urinary schistosomiasis and the first case was described in 1914. After an alarming prevalence rate (13 416 cases) in 1973, Morocco decided to establish a strategy to control and then to eliminate schistosomiasis through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Other study reported that lack of knowledge about schistosomiasis, cultural issues, as major source of problem so the motivation and compliance of both population and social workers tend to decline as morbidity become hardly visible. 13…”
Section: Discussionmentioning
confidence: 99%
“…Other study reported that lack of knowledge about schistosomiasis, cultural issues, as major source of problem so the motivation and compliance of both population and social workers tend to decline as morbidity become hardly visible. 13…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of schistosomiasis ( S. haematobium ) in Morocco has existed since historic times but is reported to have been prevented in 2004 and onwards [ 34 ]. To hinder re-emergence, subjects with positive antibody serology are required to be tested for active infection with sensitive tests.…”
Section: Can Schistosomiasis Be Eliminated?mentioning
confidence: 99%
“…Morocco, after nearly three decades of effort, was successful in the elimination of urogenital schistosomiasis caused by S. haematobium . Since 2004 no new local cases were reported [4]. In 2009 validation of interruption of transmission was commenced with the initiation of a national serological survey (using enzyme-linked immunoelectrotransfer blot, EITB) screening for human antibodies against S. haematobium in children, followed by a national molecular malacology survey analyzing the prevalence of infected snails (the intermediate host).…”
Section: Introductionmentioning
confidence: 99%